Morphology of Bacteria and Fungi From The Fermentation of Asam Drien as a Local Food Ingredient of West Aceh - Zuraidah, Zuraidah; Nursanty, Risa; Rahmi, Rahmi (Biotik, 2024)
A typical food ingredient of the Aceh region, especially the western and southern, is Asam drien (language from the West Aceh region). Asam drien is made from durian fruit meat, usually due to the abundance of durian fruit, or because the durian fruit is of poor quality such as the taste of the bland fruit meat, then most of the people utilize the durian fruit into Asam drien which can be used as a seasoning for cooking. The purpose of this study was to identify the morphological characteristics of bacterial and fungal colonies in Asam drien processing, this study used a qualitative descriptive method for colony characteristics, and biochemical tests. The results of research on bacteria and fungi in Asam drien found 14 colonies from the entire fermentation both at home and in the laboratory, namely irregular and diffuse, elongated, round, and threaded shapes; colony color characteristics obtained only one color, namely cream color; characteristics of colony edges there are 5, namely: wavy, squiggly, smooth, serrated, and threadbare. Colony elevation characteristics obtained 2 forms, namely flat and raised. There are 2 types of colony surface characteristics, namely rough and smooth shiny. Then reisolated on selective media DeMan Rogosa Sharpe Agar (MRS Agar) for lactic acid bacteria. The results of observations found 11 colonies from the entire fermentation each consisting of 2 types of isolates Ka and Kb which are Gram-positive bacteria bacillus and coccus cell forms. As well as fungi that grow on Asam drien, namely the genus Rhizopus and the type of yeast found from the genus Saccharomyces. The catalase test on Asam drien bacteria is positive, has proteolytic, amylolytic, and cellulolytic potential, but is not able to hydrolyze fat and alcohol.